DOP72 Perianal Crohn's Disease in the biologic era: A population-based cohort study. (27th May 2021) - Jenkinson, P; Plevris, N; Lyons, M; Siakavellas, S; Arnott, I; Jones, G R; Watson, A; Lees, C
Abstract: Background: Peri-anal Crohn's disease (pCD) significantly affects quality of life in patients with CD. The natural history of pCD in the era of biologic therapy is poorly understood. Perianal surgery includes examination under anaesthesia (EUA), drainage of peri-anal sepsis, seton instertion and fistula manipulation. EUA forms part of the standard of care at diagnosis of pCD and therefore can be used as a proxy for incidence of pCD. Methods: CD patients were identified from the Lothian IBD registry, a physician validated registry of all IBD cases within Lothian which has been shown to be 94.3% complete. Prospectively collected coding data was used to identify peri-anal surgery, which was validated by review of the electronic health record. Biologic prescription data was extracted from the Lothian biologics database; a physician validated, prospectively collected registry. Time trend analysis was performed for the period 2000 to 2017 by 1) calculating annual incidence rates of peri-anal interventions for all patients with CD and estimating annual percentage change and 2) by calculating cumulative incidence of pCD and biologic prescription in newly diagnosed CD and 3) stratifying by era of diagnosis (Cohort 1: 2000–2008 and Cohort 2: 2009–2017. Results: 2937 patients with CD were identified in the study period, with 1108 operations for pCD performed on 381 patients. Rates of surgery fell from 5.1 to 2.0 operations per 100 CD patients per year between 2000 and 2017 (p<0.001) giving an annual percentage change of -3.4% (-4.9% to -1.9% 95% CI) (fig 1). 1753 new diagnoses of CD were made of whom 247 developed pCD. 5 year risk of pCD was 12.8% (9.5–16.6%) with no significant difference identified between cohort 1 (11.5%) and cohort 2 (13.8%) (p=0.116) (fig 2). The 5 year incidence of biologic prescription for patients with pCD increased from 11.2% in cohort 1 to 58.1% in cohort 2 (p<0.001) (fig 3). Figure 1: Number of peri-anal interventions per 100 CD patients per year (multiple procedures per patient included). Figure 2: Kaplan Meier curves showing cumulative incidence of pCD stratified by era of diagnosis. Figure 3: Kaplan Meier curves showing cumulative incidence of biologic prescription in patients with CD stratified by era of diagnosis and presence of pCD. Conclusion: The incidence of pCD remains unchanged over time. Although we cannot ascribe causality, the overall decrease in surgery for pCD has been paralleled by a marked increase in the use of biologic medication.